2021
DOI: 10.1302/0301-620x.103b2.bjj-2020-1528.r1
|View full text |Cite
|
Sign up to set email alerts
|

Hip displacement in children with cerebral palsy

Abstract: Aims The migration percentage (MP) is one criterion used for surgery in dislocated or displaced hips in children with cerebral palsy (CP). The MP at which a displaced hip can no longer return to normal is unclear. The aim of this paper was to identify the point of no return of the MP through a large population-based study. Methods All children registered on the Cerebral Palsy Integrated Pathway Scotland surveillance programme undergo regular pelvic radiographs. Any child who had a MP measuring over 35% since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
12
2
Order By: Relevance
“…The relevant finding is that the cutoff value that resulted from the present study is not lower than Wordie’s, 21 contrary to expectations, considering the sample of GMFCS IV–V. This might be attributed to individual characteristics of the population that was examined, which is not representative of the Italian population.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The relevant finding is that the cutoff value that resulted from the present study is not lower than Wordie’s, 21 contrary to expectations, considering the sample of GMFCS IV–V. This might be attributed to individual characteristics of the population that was examined, which is not representative of the Italian population.…”
Section: Discussioncontrasting
confidence: 99%
“…This value is a little higher than the cutoff found by Wordie et al 21 (MP ≥46%), but the difference is comprised in the measurement error of ±5°, 23 so it should not be considered as significant.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…2 Children with a MP of > 40% are at a high risk of further displacement. 3,4 Hermanson et al 5 showed that a high head shaft angle (HSA) also correlates with an increased risk of displacement. The risk is higher in children with more severe functional impairment as measured using the Gross Motor Function Classification System 6 (GMFCS) and, finally, the risk is higher in younger children.…”
Section: Introductionmentioning
confidence: 99%